(untitled) (International Journal of Engineering and Computer Science, 2013)
As the peers participating in Unstructured networks interconnect randomly, they rely on flooding query messages to discover objects of interest and thus introduce Remarkable network traffic. Empirical measurement studies indicate that the peers in P2P networks have similar preferences, and have Recently proposed unstructured P2P networks that organize participating peers by exploiting their similarity. The resultant networks may not perform searches efficiently and effectively because existing overlay topology construction algorithms often create Unstructured P2P networks without performance guarantees.A novel overlay formation algorithm for unstructured P2P networks, is unique in that it poses rigorous performance guarantees. Theoretical performance results conclude that in a constant probability, searching an object in this proposed network efficiently takes hops (where c is a small constant), and the search progressively and effectively exploits the similarity of peers. This overlay approach requires a minimal number of communication over the network and provides tunable parameters to maximize performance for various network topologies. It provides a powerful technique for the aggregates of various topologies and data clustering, but comes with limitations based upon a given topologies structure and connectivity. For topologies with very distinct clusters of peers, it becomes increasingly difficult to accurately obtain random samples due to the inability of random-walk process to quickly reach all clusters.